Fluorescence lifetime correlation spectroscopy reveals compaction mechanism of 10 and 49 kbp DNA and differences between polycation and cationic surfactant - Humpolícková, Jana; Beranová, Lenka; Stĕpánek, Miroslav; Benda, Ales; Procházka, Karel; Hof, Martin (The journal of physical chemistry. B, 2008)
Within the past decade single molecule techniques contributed significantly to the understanding of the mechanism of DNA condensation induced by various kinds of condensers. While observation of single DNA molecules bigger than 100 kbp (kilobasepairs) can be achieved by fluorescence microscopy, smaller DNA molecules can be visualized directly only via methods allowing higher resolution like atomic force microscopy (AFM), with the drawback that the observed particles interfere with the surface. Here, we introduce a robust utilization of a novel technique based on the detection of single molecules, fluorescence lifetime correlation spectroscopy (FLCS). The method simultaneously determinates diffusion coefficients and fluorescence lifetime. We demonstrate that FLCS can distinguish between different compaction mechanisms of DNA molecules being even smaller than the resolution of a fluorescence microscope. The success of this unique technique is based on the fact that FLCS allows for characterizing the diffusion properties of the condensed forms exclusively in presence of uncondensed DNA molecules. We focus on the condensation mechanism of circular 10 and linear 49 kbp DNA induced by spermine and cetyltrimethylammonium bromide (CTAB). We show that spermine induces an all-or-none transition, while the condensation with CTAB is gradual. The conclusions drawn are furthermore supported by two standard techniques, dynamic light scattering (DLS), and fluorescence correlation spectroscopy (FCS).
Keywords: Spectrometry, Fluorescence; Scattering, Radiation; radiační rozptyl; povrchově aktivní látky; kationty; fluorescenční spektrometrie; Cations; Surface-Active Agents